Innovation as a factor in achieving economic competitiveness - Bakirbekova А.М.; Baktymbet, A.S.; Baktymbet, S.S. (Economic series of the Bulletin of L.N. Gumilyov ENU, 2023)
. To actively innovate the development of the economy, it is necessary to make full use of scientific and technological developments in the real sectors of the economy. Technological progress is a factor of production and a means of increasing factors of production. Those countries which will not survive the «technological race» will be pushed into a zone of impoverishment and backwardness. As a result of systematic efforts on the part of the country, innovation has been identified as a strategically important area for the development of the Republic of Kazakhstan. The State has defined the key priorities of the Third Modernization, the first of which is accelerated technological modernization and increasing the productivity of industries through the transfer of new technologies and the introduction of best practices. To reorient science and technology to a new level of innovative development, it is necessary to restructure the entire scientific and technical system of the Republic of Kazakhstan into innovative paths, which should lead to a breakthrough in all sectors of the country’s economy.